The volume is given by: V = L * Apb * h Where, L: side of the base Apb: apothema of the base h: height Substituting we have: V = (4) * ((root (3) / 2) * 4) * (6) Rewriting we have: V = (4) * ((root (3) / 2) * 4) * (6) V = 96 * (root (3) / 2) V = 48 * root (3) Answer: V = 48 * root (3)
The answer of this is V = 48 * root (3). Formula: V = L * Apb * h Where, L= side of the base Apb=apothema of the base h= heightSubstitute the values: V = (4) * ((root (3) / 2) * 4) * (6) V = (4) * ((root (3) / 2) * 4) * (6) V = 96 * (root (3) / 2) V = 48 * root (3)